Persesuaian Subjek-Verba sebagai Indikasi Basantara Santri dalam Teks Dekriptif Bahasa Arab - Azzahra, Shofannisa Alifia; Lukman, Fahmy; Krisnawati, Ekaning (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
This study is motivated by the fact that Arabic, with its complex inflectional system, poses significant challenges for students with an agglutinative mother tongue such as Indonesian, especially regarding grammatical agreement between subjects and verbs. This study aims to examine and analyze students' ability to perform grammatical agreement through written language by applying a qualitative descriptive method to investigate grammatical agreement in Arabic texts produced by 12th-grade students at a modern Islamic boarding school in Sumedang. Data collection was carried out using direct observation and analysis of descriptive text documents created by students. The analysis focused on sentences containing Arabic verbs. The linguistic data were then analyzed systematically using a distributional method to reveal patterns of grammatical agreement and the underlying basantara process. The distribution method was used to reduce the data, which was then analyzed using the distributional method. Three main strategies were used by students when dealing with subject-verb agreement in Arabic: (1) Replacement of verbs with nouns, a reflection of direct transfer from their native language, which proves that in acquiring Arabic, students tend to transfer grammatical patterns from Indonesian into Arabic texts; (2) The use of conventional verbs without change, a manifestation of overgeneralization that shows the assumption that Arabic verb formation rules are universal, thus failing to apply verb conjugation forms that match the subject; and (3) Examples of accurate subject-verb agreement, evidence of ongoing basantara development, also show an increase in accuracy in the target language acquisition process.